ANALISIS PREDATORY PRICING LIVE TIKTOK SHOP DI TENGAH PEMANFAATAN E-COMMERCE - Ariani, Ceci Dwi; Fiani, Selvia Octha; Putri, Sabila Anindiya (Pusat Riset dan Publikasi, 2025)
TikTok is a social media platform that is on the rise, not only being a space for users to share creative content, but also functioning as an e-commerce platform through the TikTok Shop feature. As an e-commerce platform, TikTok Shop offers opportunities for MSMEs to expand their market reach, but unfair business practices like predatory pricing pose a significant challenge. Predatory pricing occurs when large businesses set prices below production costs to eliminate competitors, which can cause significant losses for MSMEs. In the short term, consumers enjoy low prices, but in the long term, this practice has the potential to create a monopoly that is detrimental to consumers. Therefore, this study discusses predatory pricing practices on TikTok Shop and its impact on MSMEs in Indonesia. This study used a qualitative approach through literature review and interviews with several MSME actors. The analysis results showed that predatory pricing forces MSMEs to change their marketing strategies, which often sacrifices profit margins and product quality. Although Indonesian regulations prohibit this practice, implementation remains weak. Therefore, there is a need to strengthen regulations and strengthen the role of the Business Competition Supervisory Commission (KPPU) in overseeing unfair business practices on e-commerce platforms. This research aims to provide insight into the challenges faced by MSMEs and recommend policies that support healthy business competition in the digital era.